Pengaruh perceived organizational support terhadap organizational citizenship behavior karyawan di hotel four points by sheraton bali seminyak. - Wayan Adi Pariarta; Fanny Maharani Suarka; Putu Ratih Pertiwi (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2021)
Organizational Citizenship Behavior (OCB) is a form of behavior that exceeds the standards of employees in the organization which affected by Perceived Ogranizational Support (POS). This research is based on the still lack of employee OCB Behavior at the Four Points Hotel by Sheraton Bali Seminyak, indicated by turnover problems that exceed 10% and OCB behavior that still lacks include: there are still work results that are below standard, lack of voluntary participation from employees, and employee complaints regarding work conditions. The purpose of this study was to determine the effect of Perceived Organizational Support on Organizational Citizenship Employees at Four Points Sheraton Bali Seminyak. The population used as respondents were permanent employees and contracts totaling 79 people, while the sampling technique used was saturated sampling. Data collection techniques in research include: Observation, Interview, Literature Study, and Questionnaire. Data analysis techniques used in this study were the Instrument Test, Classical Assumption Test, Simple Linear Regression Analysis, Partial Hypothesis Test (T Test), Correlation Analysis, and Determination Coefficient Analysis. The results showed that the Perceived Organizational Support variable had a positive and significant effect on the employee's Organizational Citizenship Behavior variable. The result of the correlation coefficient analysis is 0.643 which means that the Percieved Organizational Support variable has a strong influence on the Organizational Citizenship Behavior variable of employees at the Four Points Hotel by Sheraton Bali Seminyak. The result of the coefficient of determination is 40.5, which means that the Percieved Organizational Support variable has an influence of 40.5% on the behavior of the Organizational Citizenship Behavior of employees, while the remaining 59.5% is influenced by other factors.